2022
DOI: 10.1007/s11356-022-19229-4
|View full text |Cite
|
Sign up to set email alerts
|

Will environmental information disclosure affect bank credit decisions and corporate debt financing costs? Evidence from China’s heavily polluting industries

Abstract: In the context of green nance, whether listed companies in heavily polluting industries can convert the external pressure of environmental information disclosure into internal motivation is critical to achieving environmental governance goals. This paper selects 946 listed companies of 16 heavily polluting industries in the Shanghai and Shenzhen stock markets as samples to explore whether environmental information disclosure can help companies increase bank credit support and reduce debt nancing costs to trans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 39 publications
(27 reference statements)
0
12
0
Order By: Relevance
“…This finding is in line with previous studies that have reported a stronger relationship between environmental initiatives and carbon emissions for firms in polluting industries (Haque and Ntim, 2022). This suggests that firms in polluting industries have a higher carbon footprint and thus face greater regulatory pressure and public scrutiny to reduce their carbon emissions (Du et al , 2022). This may lead them to adopt more aggressive carbon reduction initiatives than firms in non-polluting industries.…”
Section: Resultsmentioning
confidence: 99%
“…This finding is in line with previous studies that have reported a stronger relationship between environmental initiatives and carbon emissions for firms in polluting industries (Haque and Ntim, 2022). This suggests that firms in polluting industries have a higher carbon footprint and thus face greater regulatory pressure and public scrutiny to reduce their carbon emissions (Du et al , 2022). This may lead them to adopt more aggressive carbon reduction initiatives than firms in non-polluting industries.…”
Section: Resultsmentioning
confidence: 99%
“…The implementation of GCP has a negative impact on the financial performance of commercial banks, which may reduce the criteria for granting green credit. Furthermore, green credit policy (GCP) not only strengthens corporate financial constraints, but also reduces investment efficiency and the scale of debt financing, causing policy performance to be offset by corporate losses, resulting in insignificant long-term policy effects [ 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…As the main creators of environmental problems, firms in heavily polluting industries will pay more attention to the disclosure of environmental information (Du et al, 2022). Confucian culture makes people pay more attention to environmental issues, and the heavily polluting firms receive more attention and supervision from the public.…”
Section: The Influence Of Industrial Attributementioning
confidence: 99%
“…Confucian culture makes people pay more attention to environmental issues, and the heavily polluting firms receive more attention and supervision from the public. The environmental disclosure of listed firms in polluting industries is a reference for banks to make credit decisions (Du et al, 2022) and is an important element of environmental verification by national environmental authorities. Compared with non-heavily polluters, firms that do not disclose environmental information on time or disclose less are more likely to be perceived by society as having environmental violations (Nguyen et al, 2021).…”
Section: The Influence Of Industrial Attributementioning
confidence: 99%